miR-221-3p Delivered by BMMSC-Derived Microvesicles Promotes the Development of Acute Myelocytic Leukemia - Zhang, Xuewu; Xu, Yu; Wang, Jinghan; Zhao, Shuqi; Li, Jianhu; Huang, Xin; Xu, Huan; Zhang, Xiang; Suo, Shanshan; Lv, Yunfei; Zhang, Yi; Yu, Wenjuan (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: The study aims to investigate the effects of miR-221-3p in bone marrow mesenchymal stem cell (BMMSC)-derived microvesicles (MVs) on cell cycle, proliferation and invasion of acute myelocytic leukemia (AML). Methods: Bioinformatics was used to predict differentially expressed miRNAs (DEmiRNAs) in AML. The morphology of BMMSC-derived MVs was observed under an electron microscope, and the positional relation of MVs and OCI-AML2 cells was observed by a fluorescence microscope. MTT, Transwell, and flow cytometry assays were used to analyze the effects of MVs on OCI-AML2 cells. The targeted relationship between miR-221-3p and CDKN1C was detected by dual luciferase assay. Results: It was verified that miR-221-3p promoted the proliferation, invasion and migration of OCI-AML2 cells, and induced the cell cycle arrest in G1/S phase as well as inhibited cell apoptosis. Further studies showed that MVs promoted the proliferation, migration and invasion of AML, and induced the cell cycle arrest in G1/S phase through miR-221-3p. It was confirmed that miR-221-3p can directly target CDKN1C to regulate cell cycle, proliferation and invasion of AML. Conclusion: miR-221-3p in BMMSC-derived MVs regulated AML cell cycle, cell proliferation and invasion through targeting CDKN1C. miR-221-3p and CDKN1C were considered to be potential targets and biomarkers for the treatment of AML in clinic.